The effect of pH and operation mode for COD removal of slaughterhouse wastewater with Anaerobic Batch Reactor (ABR) - Maria Octoviane Dyan; Gita Permana Putra; Budiyono Budiyono; Siswo Sumardiono; Tutuk Djoko Kusworo (Waste Technology, 2015)
Disposal of industrial wastes in large quantities was not in accordance with today's standards of waste into environmental issues that must be overcome with proper treatment. Similarly, the abattoir wastewater that contains too high organic compounds and suspended solids. The amount of liquid waste disposal Slaughterhouse (SW) with high volume also causes pollution. The research aim to resolve this problem by lowering the levels of BOD-COD to comply with effluent quality standard. Anaerobic process is the right process for slaughterhouse wastewater treatment because of high content of organic compounds that can be utilized by anaerobic bacteria as a growth medium. Some research has been conducted among abattoir wastewater treatment using anaerobic reactors such as ABR, UASB and ASBR. Our research focuses on the search for the optimum results decline effluent COD levels to match the quality standards limbah and cow rumen fluid with biodigester ABR (Anaerobic Batch Reactor). The variables used were PH of 6, 7, and 8, as well as the concentration ratio of COD: N is 400:7; 450:7, and 500:7. COD value is set by the addition of N derived from urea [CO(NH2) 2]. COD levels will be measured daily by water displacement technique. The research’s result for 20 days seen that optimum PH for biogas production was PH 7,719 ml. The optimum PH for COD removal is PH 6, 72.39 %. The operation mode COD:N for biogas production and COD removal is 500:7, with the production value is 601 ml and COD removal value is 63.85 %. The research’s conclusion, the PH optimum for biogas production was PH 7, then the optimum PH for COD removal is PH 6. The optimum operation mode COD:N for biogas production and COD removal was 500:7